The Effect of Bundle Care Implementation on Reducing the Incidence of Nosocomial Infections in ICU Patients - Serly Sani Mahoklory; Rezqiqah Aulia Rahmat (International Journal of Health Sciences, 2025)
Background:Nosocomial infections are a common complication in patients treated in the Intensive Care Unit (ICU). Critical patient conditions, the use of invasive devices, and long hospital stays increase the risk of nosocomial infections. One recommended prevention strategy is the implementation of bundled care, which consists of a series of evidence-based actions consistently implemented. Objective: This study aims to analyze the effect of bundled care implementation on reducing the incidence of nosocomial infections in ICU patients. Method:This study used a quasi-experimental design with a pretest–posttest approach without a control group. The study sample consisted of 50 ICU patients selected using a purposive sampling technique. Data on the incidence of nosocomial infections were collected before and after the implementation of bundle care for 30 days. Data analysis was performed using a paired t-test with a significance level of p < 0.05. Results: The results showed a significant decrease in the incidence of nosocomial infections after the implementation of bundle care, with a p value of < 0.001. Conclusion:Consistent implementation of bundle care is effective in reducing the incidence of nosocomial infections in ICU patients.